Association between chronic kidney disease and carotid intima-media thickness in relation to circulating CD34-positive cell count among community-dwelling elderly Japanese men. (April 2019) - Shimizu, Yuji; Yamanashi, Hirotomo; Noguchi, Yuko; Koyamatsu, Jun; Nagayoshi, Mako; Kiyoura, Kairi; Fukui, Shoichi; Tamai, Mami; Kawashiri, Shin-Ya; Kondo, Hideaki; Maeda, Takahiro
Abstract: Background and aims: Endothelial injury is well-known as a process that can lead to chronic kidney disease (CKD) and atherosclerosis. Hematopoietic activity is known to be associated inversely with CKD and positively with atherosclerosis. Since bone-derived progenitor cells (CD34-positive cells) contribute to endothelial repair (including the progression of atherosclerosis), understanding the association between CKD and carotid intima-media thickness (CIMT), in relation to circulating CD34-positive cell count, may be an efficient means of clarifying the mechanisms underlying endothelial activity. Methods: We conducted a cross-sectional study of 570 elderly Japanese men aged 60–69 years, who underwent a general health check-up. Participants were stratified as per a median circulating CD34-positive cell count (1.01 cells/μL). Results: Independent of the known cardiovascular risk factors, CIMT was found to be positively associated with CKD in the participants with high circulating CD34-positive cell counts but not in participants with low counts. Odds ratios were 1.40 (1.04, 1.89) for participants with high and 1.01 (0.72, 1.43) for participants with low circulating CD34-positive cell counts after adjustment for known cardiovascular risk factors at 95% confidence intervals for CKD with one standard deviation increment of CIMT. Conclusions: A positive association between CIMT and CKD was observed among participants with high circulating CD34-positive cell counts but not among participants with low counts. Endothelial repair activity might determine the association between CKD and CIMT. Graphical abstract: Image 1 Highlights: Carotid intima-media thickness (CIMT) was associated with chronic kidney disease (CKD) in participants with a high CD34+ cell count. No association was observed for participants with a low CD34+ cell count. Endothelial repair activity might determine those associations.